Lexical hub of content in the self-organization process of text and discourse on the background of Senegalese tradition - - Fatu Faye Diop (RUDN Journal of Language Studies, Semiotics and Semantics, 2016)
The article deals with a hierarchical system of lexical hub of the content of the text, as part of the coatings of the author, formed in the process of creation of text, reflecting, on the one hand, the language personality of the author, and on the other hand, are created by the author of the text possible worlds. In this sense, the lexical hub of the content of synergies and prone to self-development in the process of creation.